Penerapan Media Lintasan Untuk Meningkatkan Kemampuan Pemahaman Tema 1 Subtema 1 Pada Siswa Sekolah Dasar - Rampai Cantika Gusvinda Afiatni; Hendra Erik Rudyanto; Fida Rahmantika Hadi (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2024)
The purpose of this study was to improve students' understanding of theme 1 subtheme 1 social studies content at SDN 2 Ngraho, Blora Regency. The method of classroom action research (PTK) was used in this study. This method consists of four stages: planning, action, observation, and reflection. The study involved thirteen students from grade VI of SDN 2 Ngraho, 11 boys and 2 girls respectively. This method uses examination. The pre-cycle class average score rose from 57.84 in the first cycle to 59.76 in the second cycle and 79.61 in the third cycle, indicating that the use of track media improved learning outcomes. The learning outcomes of students who achieved the KKM rose from 40% to 55% in cycle I and to 85% in cycle II, but dropped from 60% in the pre-cycle.